2016
DOI: 10.1016/j.chemosphere.2016.03.128
|View full text |Cite
|
Sign up to set email alerts
|

Organic contaminants in western pond turtles in remote habitat in California

Abstract: h i g h l i g h t sOrganic pollutants are widespread in a California turtle with conservation status. Pesticides were prominent in Sequoia National Park downwind of heavy agriculture. PCBs and PAHs are associated with watersheds having historic mines and mills. HUP and PCB concentrations indicate potential bioaccumulation is occurring. a r t i c l e i n f o b s t r a c tRemote aquatic ecosystems are exposed to an assortment of semivolatile organic compounds (SOCs) originating from current and historic uses, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
1
1
Order By: Relevance
“…In terms of occurrence of POPs, our results in European pond turtles were low compared to other studies (Bucchia et al 2015; Meyer et al 2016). The occurrences of DL‐PCBs in 8% of European pond turtles, as well as p,p′‐DDE in 2% of individuals, were much lower than those found in plasma of loggerhead sea turtles, which ranged from 63% in the Atlantic Ocean to 100% in the Adriatic Sea for DL‐PCBs and 100% for p,p′‐DDE (Bucchia et al 2015).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In terms of occurrence of POPs, our results in European pond turtles were low compared to other studies (Bucchia et al 2015; Meyer et al 2016). The occurrences of DL‐PCBs in 8% of European pond turtles, as well as p,p′‐DDE in 2% of individuals, were much lower than those found in plasma of loggerhead sea turtles, which ranged from 63% in the Atlantic Ocean to 100% in the Adriatic Sea for DL‐PCBs and 100% for p,p′‐DDE (Bucchia et al 2015).…”
Section: Discussioncontrasting
confidence: 93%
“…Snapping turtles are freshwater turtles with similar feeding habits to those of European pond turtles; snapping turtles also consume plant and animal matter, including aquatic invertebrates, fish, frogs, and reptiles (Ernst et al 1994). Other studies of turtles documented plasma concentrations of POPs comparable to those in our study; for instance, for PCB-153 and HCB in another freshwater species, the western pond turtle (Actinemys marmorata), in Sequoia National Park, USA, in 2012 (Meyer et al 2016), as well as in marine turtles such as loggerhead sea turtles (Caretta caretta) in the eastern Atlantic Ocean in 2011 and 2012 (Bucchia et al 2015) and in green turtles (Chelonia mydas) and hawksbill turtles (Eretmochelys imbricata) in Cape Verde in 2009 to 2011 (Camacho et al 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Hall et al (1983) reported concentrations of petroleum hydrocarbons in tissues of sea turtles exposed to oil after the Ixtoc spill in the Bay of Campeche, Mexico, in 1979. In freshwater turtles, studies have focused on PAH concentrations in eggs and subcutaneous fat (Bell et al 2006, Holliday et al 2008, Rowe et al 2009) or blood (Drabeck et al 2014, Meyer et al 2016) of turtles from known contaminated habitats. In general, information is lacking on baseline exposure, uptake and tissue distribution of parent and alkylated PAH homologs for juvenile and adult turtles.…”
Section: Contribution To the Theme Section 'Effects Of The Deepwater mentioning
confidence: 99%